1986
DOI: 10.1037/0096-1523.12.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Reflection in preferences under risk: Who and when may suggest why.

Abstract: Conventional economic theory assumes that people are uniformly risk averse. Psychological studies, however, have shown that people are sometimes risk averse for gains but risk seeking for losses, a phenomenon termed the reflection effect. The robustness of the reflection effect was examined both within subjects and across subjects differing in risk style for a set of multi-outcome lotteries. Reflection was found to be weak and irregular for all choice pairs except those that included a lottery with a riskless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
185
1
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 22 publications
18
185
1
2
Order By: Relevance
“…In this study, we tested this aspect of decision-making using the 'gains only' and 'losses only' trials in which participants chose between certain gains vs gambles to earn greater gains or no gains (inducing risk-aversion), or between certain losses vs gambles to suffer no loss or suffer still larger losses (inducing risk-seeking decisions)Fthe so-called 'reflection effect' (Schneider and Lopes, 1986). On these trials, there was no indication that THC attenuated the natural tendency to choose the risk-averse option in the former case and the risk-seeking option in the latter case compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we tested this aspect of decision-making using the 'gains only' and 'losses only' trials in which participants chose between certain gains vs gambles to earn greater gains or no gains (inducing risk-aversion), or between certain losses vs gambles to suffer no loss or suffer still larger losses (inducing risk-seeking decisions)Fthe so-called 'reflection effect' (Schneider and Lopes, 1986). On these trials, there was no indication that THC attenuated the natural tendency to choose the risk-averse option in the former case and the risk-seeking option in the latter case compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Neither option offered any associated gains. Within both the 'gains only' and 'losses only' trials, the expected value of each gamble was equal; however, decision-makers usually exhibit a marked risk-aversion in the former case (ie choice of the guaranteed gain of 40 points) but marked risk-seeking behavior in the latter case (ie choice of the gamble with a 0.5 chance of losing 80 points and a 0.5 chance of losing 0 points) (Schneider and Lopes, 1986). The dependent measures for the 'gains only' trials and the 'losses only' trials were the proportion of trials on which the participants chose the guaranteed outcome and the associated mean deliberation time (ms) for these choices.…”
Section: Decision-making Taskmentioning
confidence: 99%
“…Not surprisingly, security motivation (risk aversion) is the far more connon pattern (see Lopes, 1984;Schneider & Lopes, in press), so cormon, in fact, that economists have considered it to be the pattern for Everyman (Arrow, 1971;Pratt, 1964). This is probably not due to chance.…”
Section: A Factor 1: Security Versus Potentialmentioning
confidence: 99%
“…Work-with-others choicles produced a constant $0.50 each block. Risky-choice research has shown that when subjects are presented with choices between options dHlivering constant (i.e., certain) and variable amounts of money with the same mean value, the constant option is typically preferred (e.g., Kahneman & Tversky, 1979;Lane & Cherek, 2001;Schneider & Lopes, 1986). Thus, a second aim of Experiment 2 was to investigate the effects of within-block variability in earnings on sharing.…”
Section: Methodsmentioning
confidence: 99%